Renal involvement of a patient with Crohn´s disease: A case report - Snížková, Olga; Jančová, Eva; Honsová, Eva (Ceskoslovenska patologie, 2021)
Inflammatory bowel disease (IBD) is a group of chronic relapsing intestinal inflammatory processes primarily represented by ulcerative colitis (UC) and Crohn´s disease (CD). Nearly half of IBD cases are followed by extraintestinal complications and renal involvement can occur independatly or along with other complications and are described with the patients sufferring from UC or CD. Most frequent renal involvement is nephrolithiasis, tubulointerstinal nephritis, different kinds of glomerulonephritis and AA amyloidosis. We are presenting an unusal form of renal involvement of a young female patient with a severe form of Crohn´s disease treated with recombinant monoclonal antibodies.
Keywords: Crohnova nemoc; recidiva; Recurrence; Female; Glomerulonephritis; kidney biopsy; glomerulonefritida; idiopatické střevní záněty; Humans; ženské pohlaví; Crohn Disease; Inflammatory Bowel Diseases; Crohn´s disease; lidé; Inflammatory bowel disease; Colitis, Ulcerative; ulcerózní kolitida; glomerulonephritis